Augmented Reality Book Media Based on A Constructivist Approach on Improving Students’ Cognitive Abilities in The Five Senses Material - Dwi Retno Sriwahyuni; Achmad Buchori; Joko Sulianto (Universitas Pendidikan Ganesha, 2025)
This research focuses on the development of Augmented Reality Book media integrated with the Constructivism approach. The goal is to produce a product that meets the criteria of validity, practicality, and effectiveness in improving the cognitive abilities of fourth-grade students on the five senses material. This research adopts the Research and Development (R&D) method using the 4-D development model, which consists of four systematic stages. The subjects of the research were fourth-grade students Elementary School. Product validation was carried out by two experts (media experts and material experts), while the practicality test was measured through teacher and student response questionnaires. The effectiveness test was measured using a Pretest Posttest Control Group Design and analyzed through the N-Gain Score. The results of the study indicate that the developed product is very feasible and valid for use, with an average validity of media experts reaching 95.19% and validity of material experts 97.11%, both of which are included in the Very Valid category. The practicality test also generated high responses from students (94%) and teachers (91%), who confirmed that the product was very practical. The key finding was the results of the effectiveness test, where the average N-Gain score in the experimental class reached 80.49 (or 0.8049), which is classified as high. This significant increase indicates that the Augmented Reality Book media with a Constructivist Approach is effective in improving students' cognitive abilities in the five senses material.